Pemetaan Potensi Ekonomi untuk Mendukung Pengembangan Usaha di Desa Maitara Selatan Kecamatan Tidore Utara Kota Tidore Kepulauan - Daud Hasim; Zulkifli Zulkifli; Musdar Muhammad; M.Iksan Umsohy (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
The purpose of this community service activity is to provide information and assist the community, especially the management of Village-Owned Enterprises (BUMDes) and the South Maitara village government, North Tidore district, related to increasing community capacity based on local resources, as an effort to improve the community's economy. Service activities are carried out for a month. Activities began with socialization in forming understanding in business and superior village economy, simulation of mapping Village Potential and assistance in marketing plans and targets. PKM results;, Maitara village has quite extraordinary potential, there is fishery potential or many Maitara village people as fishermen, there is also tourism potential, natural wealth. Become a problem in developing village potential.